2022
DOI: 10.3390/ijms24010304
|View full text |Cite
|
Sign up to set email alerts
|

Mycosynthesis of Metal-Containing Nanoparticles—Synthesis by Ascomycetes and Basidiomycetes and Their Application

Abstract: Fungi contain species with a plethora of ways of adapting to life in nature. Consequently, they produce large amounts of diverse biomolecules that can be generated on a large scale and in an affordable manner. This makes fungi an attractive alternative for many biotechnological processes. Ascomycetes and basidiomycetes are the most commonly used fungi for synthesis of metal-containing nanoparticles (NPs). The advantages of NPs created by fungi include the use of non-toxic fungus-produced biochemicals, energy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 196 publications
(251 reference statements)
0
2
0
Order By: Relevance
“…Among other bioactive compounds, mushroom extracts are a great source of riboflavin. According to recent research, copper nanoparticles are formed by the flavoproteins found in mushroom extracts (17) . In a similar study a team of researchers discovered that pine mushroom flavoproteins are essential for the production of silver nanoparticles (18) .…”
Section: Resultsmentioning
confidence: 99%
“…Among other bioactive compounds, mushroom extracts are a great source of riboflavin. According to recent research, copper nanoparticles are formed by the flavoproteins found in mushroom extracts (17) . In a similar study a team of researchers discovered that pine mushroom flavoproteins are essential for the production of silver nanoparticles (18) .…”
Section: Resultsmentioning
confidence: 99%
“…are additional fungi that offer numerous advantages. These include diverse survival strategies, ease of biomass handling, the capacity to multiply using straightforward culture media, tolerance to high metal concentrations, and enhanced productivity in terms of nanoparticle production from WPCBs [ 114 ].…”
Section: Green Synthesis Of Nanoparticles From Wpcbsmentioning
confidence: 99%
“…Processes reliant on cellular metabolism, collectively known as bioaccumulation, encompass the transportation of metals across the cell wall and their subsequent localization within specific cellular compartments [11,12]. Numerous microorganisms, including filamentous fungi and yeasts, have demonstrated the capability to accumulate toxic metals within their cellular structures [13,14]. Bioaccumulation is categorized as a physiological mechanism for metal immobilization that is dependent upon cellular metabolism.…”
Section: Characteristics Of the Ostramo Lagoons Sitementioning
confidence: 99%